Pengaruh Pengetahuan Pajak dan Keadilan Pajak terhadap Kepatuhan Wajib Pajak UMKM di Perum Mega Regency Kabupaten Bekasi - Sri Wahyuni; Sopian Sopian; Aditya Santoso (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
Tax compliance of Micro, Small and Medium Enterprises (MSMEs) is a critical factor in optimizing state tax revenues. This study aims to analyze the effect of tax knowledge and tax fairness on MSME taxpayer compliance. The research methodology uses a quantitative approach with multiple regression analysis techniques. The research data were obtained through a survey of 76 MSME taxpayer respondents. Hypothesis testing was carried out using the T-test for partial hypotheses and the F-test for simultaneous hypotheses. The practical implications of this study are the need for intensification of tax education programs and improvement of the tax fairness system by the government. This study provides theoretical contributions to the development of tax compliance theory, especially in the context of MSMEs in Indonesia. The limitations of the study lie in the limited geographical scope, so further research is recommended to expand the scope of the area and explore other moderating variables.